Considerations about the impact of public lighting on pedestrians' perception of safety and well-being. (November 2016) - Peña-García, A.; Hurtado, A.; Aguilar-Luzón, M.C.
Highlights: Fundamentals are sometimes forgotten when dealing with advances concepts. This extension to the previous results in a deeper approach to some concepts. The proposals inFotios (2016) are helpful to review and think about basic concepts. Abstract: One recent Comment proposed some remarks concerning the study entitled "Impact of public lighting on pedestrians' perception of safety and well-being". This study presents some considerations about the Comment and clarifies some points of our previous study that might have not been well understood.